2014
DOI: 10.1074/jbc.m113.537068
|View full text |Cite
|
Sign up to set email alerts
|

A Frustrated Binding Interface for Intrinsically Disordered Proteins

Abstract: Background: Protein-protein interactions often involve intrinsically disordered protein domains. Results: The binding interface between two disordered protein domains is suboptimal, or frustrated, with regard to the energetics. Conclusion:The frustration likely results from the promiscuous binding behavior of these disordered domains. Significance: Suboptimal binding interfaces may be common among intrinsically disordered proteins with multiple binding partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 38 publications
4
43
0
1
Order By: Relevance
“…The Φ value analysis represents the only experimental method available to describe the structure of a transition state and it has been employed extensively to describe the mechanism of folding of globular proteins (62,63), and lately the coupled binding and folding of IDPs (36)(37)(38)40,48,50,59,60,(64)(65)(66)(67)(68)(69)(70)(71)(72)(73). Interestingly, it has been generally observed that Φ values tend to be between zero and one, with very few cases of unusual values (i.e.…”
Section: The Structure Of the Transition State: φ Value Analysismentioning
confidence: 99%
“…The Φ value analysis represents the only experimental method available to describe the structure of a transition state and it has been employed extensively to describe the mechanism of folding of globular proteins (62,63), and lately the coupled binding and folding of IDPs (36)(37)(38)40,48,50,59,60,(64)(65)(66)(67)(68)(69)(70)(71)(72)(73). Interestingly, it has been generally observed that Φ values tend to be between zero and one, with very few cases of unusual values (i.e.…”
Section: The Structure Of the Transition State: φ Value Analysismentioning
confidence: 99%
“…The entries also vary in the degree of structural order. While most correspond to interactions between folded domains, the database contains entries in which structuring occurs upon binding, such as protein-peptide interactions and, in the extreme case, the ACTR/NCBD interaction in which both binding partners become ordered upon binding [32]. Indeed, the requirements of having a structure in order to be included in the data set, ipso facto biases the data, and means that there is no representation of "fuzzy" complexes in which a diffuse structural ensemble in the bound state prevents the formation of a resolvable crystal.…”
Section: A Diversity Bias and Interrelationships Within Skempimentioning
confidence: 99%
“…The binding reaction involves several steps, as evidenced from the multiple kinetic phases observed in stopped flow spectroscopy and single molecule-FRET experiments [16][17][18] . It is however not clear what all kinetic phases corresponds to and equilibrium data agree well with the major kinetic binding phase 19 in overall agreement with a two-state binding mechanism.…”
Section: Introductionmentioning
confidence: 83%
“…These binding partners include among others the transcription factors and transcriptional co-regulators p53, IRF3 and NCOA1, 2 and 3 (also called SRC, TIF2 and ACTR, respectively). The interaction between NCBD and the CBP-interacting domain (CID) from NCOA3 (ACTR) has been intensively studied with kinetic methods to elucidate details about the binding mechanism [13][14][15][16] . These protein domains interact in a coupled folding and binding reaction in which CID forms two to three helices that wrap around NCBD 10 .…”
Section: Introductionmentioning
confidence: 99%